Characterization of hemodynamics in anomalous aortic origin of coronary arteries using patient-specific modeling. (February 2022) - Chidyagwai, Simbarashe G.; Vardhan, Madhurima; Kaplan, Michael; Chamberlain, Reid; Barker, Piers; Randles, Amanda
Abstract: The anomalous aortic origin of coronary arteries (AAOCA) is a congenital disease that can lead to sudden cardiac death (SCD) during strenuous physical activity. Despite AAOCA being the second leading cause of SCD among young athletes, the mechanism behind sudden cardiac death remains mostly unknown. Computational fluid dynamics provides a powerful tool for studying how pathologic anatomy can affect different hemodynamic states. The present study investigates the effect of AAOCA on patient hemodynamics. We performed patient-specific hemodynamic simulations of interarterial AAOCA at baseline and in the exercise state using our massively parallel flow solver. Additionally, we investigate how surgical correction via coronary unroofing impacts patient blood flow. Results show that patient-specific AAOCA models exhibited higher interarterial time-averaged wall shear stress (TAWSS) values compared to the control patients. The oscillatory shear index had no impact on AAOCA. Finally, the coronary unroofing procedure normalized the elevated TAWSS by decreasing TAWSS in the postoperative patient. The present study provides a proof of concept for the potential hemodynamic factors underlying coronary ischemia in AAOCA during exercise state.